The Mesozoic exhumation history of the Karatau-Talas range, western Tian Shan, Kazakhstan-Kyrgyzstan - Jepson, Gilby; Glorie, Stijn; Khudoley, Andrey K.; Malyshev, Sergey V.; Gillespie, Jack; Glasmacher, Ulrich A.; Carrapa, Barbara; Soloviev, Alexei V.; Collins, Alan S. (Tectonophysics, 2021)
The Tian Shan mountain range maintains high topography across the Eurasian continent despite being distal to any modern plate boundary. Previous studies of the Tian Shan have revealed a history of mountain building in response to India-Asia collision which has overprinted much of its Mesozoic history. The Karatau and Talas ranges in the north-western Tian Shan represent a unique opportunity to investigate the erosional response to the Mesozoic tectonics of Central Asia. In this study, we present medium-to-low temperature thermochronology and thermal history modelling from a series of Neoproterozoic to Permian sedimentary and granitoid samples taken from the Karatau and Talas ranges. Our results identify three phases of late Paleozoic-Mesozoic deformation and exhumation: (1) a regional orogenic event in the Permian-Early Triassic (ca. 280-240 Ma) related to the final amalgamation of the Central Asian Orogenic Belt, (2) Late Triassic-Early Jurassic (ca. 230-190 Ma) reactivation in response to the collision of the Qiangtang block with the Eurasian margin, and a (3) phase of rapid basement cooling during the Late Jurassic-Early Cretaceous (ca. 160-140 Ma), associated with the closure of the Meso-Tethys Ocean. These results suggest that the Karatau and Talas ranges preserves extensive Mesozoic erosional signatures, which developed in response to Eurasian amalgamation of Central Asia and progressive closure of the Tethys Ocean.
Gesehen am 21.10.2021